NEUROECONOMICS AND REINFORCEMENT LEARNING. AN EXPLORATORY ANALYSIS - Chavaglia, J. N.; Filipe, J. A.; Ferreira, M. A. M. (15th Conference on Applied Mathematics 2016-Proceedings, 2016)
In an era in which the study of the brain gets increasingly featured as an analytical tool of economic phenomena, the understanding of the way Neuroeconomics works as a tool for managers, students and other economic agents is now particularly important. There is now a need to have research that allow the clarification of the analytical decision process and the potential of brain study for decision making process of economic agents. Considering this new reality, a study is presented concerning one of the most important issues for the decision maker, which is the reinforcement learning process.